Comparative studies on the weldability, microstructure and tensile properties of autogeneous TIG welded AISI 430 ferritic stainless steel with and without flux. (October 2015) - Ramkumar, K. Devendranath; Chandrasekhar, Aditya; Singh, Aditya Kumar; Ahuja, Sharang; Agarwal, Anurag; Arivazhagan, N.; Rabel, Arul Maxiumus
Abstract: This research study aims at investigating the weldability of ferritic stainless steel, AISI 430 by tungsten inert gas (TIG) welding technique with and without the use of activated fluxes. In the Activated flux TIG (A-TIG) welding process, two different fluxes SiO2 and Fe2 O3 have been used to compare the geometric and metallurgical characteristics of the weld beads of AISI 430. It was inferred from the bead on studies that the depth of penetration and the bead width varies with varying the welding current. Microstructure studies depicted the presence of two phase structure containing ferrite-intergranular martensite and the precipitate-free zone surrounding the grain boundary martensite at the fusion zone of all the weldments. Tensile failures were observed at the parent metal of AISI 430 without flux addition and while employing SiO2 flux; whereas at the fusion zone for Fe2 O3 flux assisted weldments. A detailed structure–property relationship of the weldments with and without flux additions are elaborated in the present study.